Pelaksanaan Outbound di Pondok Pesantren Assa’adah 3 Ciseeng Tahun 2022 - Gatot, Edwin Sena Andiana; Azizah, Rahmah Putri; Aryasatya, Ilham Aryasatya; Nurulia, Fatma (Educationist: Journal of Educational and Cultural Studies, 2024)
Real Work Lecture (RWL) is an intra-curricular form which is an implementation of the Tridharma of Higher Education to provide students with work and learning experiences in community empowerment. Real work college activities are a golden opportunity for smart, critical, innovative and creative students in finding the right solutions, formulas and strategies for various problems and developments that exist in the village. The placement of RWL student locations is mostly directed at locations that have superior potential but are still minimal. This is a challenge for groups of real lecture participants to change the existing village's superior potential with economic value through work programs that will be directly assisted by practitioners and the academic community. The method of community service carried out by RWL students is through fun learning and evaluation of RWL activities. The target in this activity is the community around the RWL location which consists of santri and female boarding school students.